“Confirmation Statements” and Cosmic Unity in John’s Apocalypse - Slater, Thomas B. (Interpretation, 2026)
The book of Revelation includes seven “confirmation statements” (1:2, 9; 6:9; 12:11, 17; 14:12; 20:4). These seven passages assure the members of the seven churches in Roman Asia that their faithfulness will be rewarded and that they have secured their place in the New Jerusalem. These statements are examples of parallelism, a common feature in Hebrew poetry, when the first statement is echoed, completed, or contrasted by a second. When viewed collectively, these seven statements say something about God Almighty, Christ Jesus, the demands of Christian discipleship, and Christian community. As a result, these seven statements establish a sacred universe, which includes both heavenly and earthly realms.